Alcohol‐related diagnoses and increased mortality in acute myocardial infarction patients: An analysis of the nationwide inpatient sample. Issue 8 (4th April 2016) - Yedlapati, Siva Harsha; Mendu, Anuradha; Stewart, Scott H.
Abstract : BACKGROUND: Moderate alcohol consumption has been associated with lower risk of coronary heart disease death, but heavy alcohol consumption may increase risk. OBJECTIVE: We sought to determine the association of alcohol‐related diagnoses with in‐hospital mortality in patients with acute myocardial infarction (AMI). DESIGN/SETTING/PATIENTS: Discharge data collected from all admissions recorded in the Nationwide Inpatient Sample (NIS) database from 2011. A cross‐sectional analysis was performed using regression methods appropriate for the NIS sample design. MEASURES: The outcome measures were in‐hospital mortality, length of stay, and cardiac procedures. RESULTS: AMI accounted for 610, 963 (1.9%) of adult in‐patient admissions, with an in‐hospital mortality rate of 5.3%. Alcohol‐related diagnoses were associated with increased mortality in AMI patients after controlling for factors associated with alcoholism including age, sex, liver disease, hypertension, diabetes, renal failure, peripheral vascular disease, arrhythmias, drug abuse, gastrointestinal bleed, and smoking (adjusted odds ratio [OR]: 1.5, 95% confidence interval [CI]: 1.2‐1.7, P < 0.001). This association was significant in both ST‐elevation myocardial infarction patients (adjusted OR: 1.7, 95% CI: 1.4‐2.2, P < 0.001) and non–ST‐elevation myocardial infarction patients (adjusted OR: 1.3, 95% CI: 1.0‐1.7, P = 0.025). Chronic alcohol‐related diagnoses were significantly associated with death, but acute alcohol effects (as estimated by withdrawal and intoxication) were not associated. CONCLUSION: Chronic alcohol‐related diagnoses were associated with a modest increase in the risk for death in individuals presenting with AMI. This risk was not accounted for by common alcohol‐related comorbidities. As a component of global efforts to limit hospital deaths from AMI, future research should identify the factors underlying this association. Journal of Hospital Medicine 2016;11:563–567. © 2016 Society of Hospital Medicine